Representaciones femeninas de Capucuy. El rol de la mujer en la Amazonía ecuatoriana antes del contacto hispánico. - Solórzano Venegas, María Soledad (2017)
The ceramic type Capucuy was defined in 2007 during a mitigation archaeological project in the area around the Limoncocha Lagoon, on the right bank of the Napo River. Among the elements of their material culture, which is linked to the period of Regional Development, it must be highlighted the presence of anthropomorphic representations, mainly backs of women where they have been shaped different stages of their lives: puberty, pregnancy and lactation. The stories of sixteenth -century travelers, particularly those associated with Orellana's expedition, reveal that the role of women in the human groups that inhabited the Amazon was far from the worldview of the conquerors, breaking schemes that led to generate the 'myth of the Amazons'. The information retrieved from the archaeological record, along with ethnohistorical and ethnographic data, allowed us to make projections that facilitate the understanding of the relevance of the female role for tropical forest societies in the Amazon foothills prior to the Hispanic contact, which was displaced to a second mainly due to a double stigma: women and indigenous people. http://www.ijsa.syllabapress.us/issues/articles/ijsa00064.html